การเลือกปฏิบัติต่อสตรี: Discrimination against Women - ไม้ทองดี นวลพรรณ (Journal of Applied Economics and Management Strategy, 2014)
บทความนี้มีวัตถุประสงค์เพื่อศึกษาถึงการเลือกปฏิบัติต่อสตรีในบริบทของประเทศไทย การให้คำนิยามและการจำแนกประเภทของการเลือกปฏิบัติโดยทั่วไปและการเลือกปฏิบัติในตลาดแรงงาน ซึ่งการทราบความหมายของการเลือกปฏิบัตินั้นจะเป็นจุดเริ่มต้นของการทำความเข้าใจถึงประเภทหรือลักษณะของการเลือกปฏิบัติในรูปแบบต่างๆ ได้ โดยอาศัยแนวคิดและทฤษฎีทางเศรษฐศาสตร์ในเรื่องการเลือกปฏิบัติมาเป็นแนวทางในการวิเคราะห์และวัดการเลือกปฏิบัติโดยเฉพาะในประเภทของการเลือกปฏิบัติค่าจ้าง แม้ว่าเกือบทุกประเทศจะมีกฎหมายต่อต้านการเลือกปฏิบัติ แต่การเลือกปฏิบัติก็ยังคงอยู่ This paper intends to consider the discrimination against women in Thailand. Definitions and types of discrimination in general and in the labor market are discussed. Knowing the meaning of discrimination is a good start for understanding various forms of discrimination. In order to analyze discrimination especially gender wage discrimination, this paper studies economic theories or models involving different types of discrimination and how to measure discrimination. Although many countries have anti-discrimination laws or policies, discrimination still exists notwithstanding.